Comparative transcriptomics of high-altitude Vulpes and their low-altitude relatives - Lyu, Tianshu; Yang, Xiufeng; Zhao, Chao; Wang, Lidong; Zhou, Shengyang; Shi, Lupeng; Dong, Yuehuan; Dou, Huashan; Zhang, Honghai (Frontiers in Ecology and Evolution, 2022)
The harsh environment of Qinghai-Tibet Plateau (QTP) imposes strong selective stresses (e.g., hypoxia, high UV-radiation, and extreme temperature) to the native species, which have driven striking phenotypic and genetic adaptations. Although the mechanisms of high-altitude adaptation have been explored for many plateau species, how the phylogenetic background contributes to genetic adaption to high-altitude of Vulpes is largely unknown. In this study, we sequenced transcriptomic data across multiple tissues of two high-altitude Vulpes (Vulpes vulpes montana and Vulpes ferrilata) and their low-altitude relatives (Vulpes corsac and Vulpes lagopus) to search the genetic and gene expression changes caused by high-altitude environment. The results indicated that the positive selection genes (PSGs) identified by both high-altitude Vulpes are related to angiogenesis, suggesting that angiogenesis may be the result of convergent evolution of Vulpes in the face of hypoxic selection pressure. In addition, more PSGs were detected in V. ferrilata than in V. v. montana, which may be related to the longer adaptation time of V. ferrilata to plateau environment and thus more genetic changes. Besides, more PSGs associated with high-altitude adaptation were identified in V. ferrilata compared with V. v. montana, indicating that the longer the adaptation time to the high-altitude environment, the more genetic alterations of the species. Furthermore, the result of expression profiles revealed a tissue-specific pattern between Vulpes. We also observed that differential expressed genes in the high-altitude group exhibited species-specific expression patterns, revealed a convergent expression pattern of Vulpes in high-altitude environment. In general, our research provides a valuable transcriptomic resource for further studies, and expands our understanding of high-altitude adaptation within a phylogenetic context.